2014
DOI: 10.2203/dose-response.13-042.shimura
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose-Gamma Rays on the Immune System of Different Animal Models of Disease

Abstract: ᮀ We reviewed the beneficial or harmful effects of low-dose ionizing radiation on several diseases based on a search of the literature. The attenuation of autoimmune manifestations in animal disease models irradiated with low-dose γ-rays was previously reported by several research groups, whereas the exacerbation of allergic manifestations was described by others. Based on a detailed examination of the literature, we divided animal disease models into two groups: one group consisting of collagen-induced arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 139 publications
(230 reference statements)
1
15
0
Order By: Relevance
“…Animals were divided randomly into 8 groups (6 animals per group): Group 1 (Control): Healthy animals supplied distilled water by gastric intubation daily for 4 weeks. Group 2 (BA): According to Mishra et al (2011), 23 Rats were treated orally with boswellic acid (BA) by gastric intubation in a dose of 50 mg/kg body weight a day for 4 weeks. Group 3 (IR): Rats were exposed to a single dose (0.5 Gy) of ionizing radiation as a low dose of radiation according to Shimura & Kojima (2014). 24 Group 4 (BA + IR): Rats were treated orally with BA every day at the same dosage as group 2 for 4 weeks, and were exposed to a single dose of IR (0.5 Gy). Group 5 (BPA): According to Amaravathi et al (2012), 25 Rats were treated orally with 500 mg/kg body weight Bisphenol A (BPA) daily over 4 weeks. Group 6 (BPA + BA): Rats were orally treated with BPA daily for 4 weeks at the same dose given to group 5 then treated with BA daily for another 4 weeks at the same dose given to group 2. Group 7 (BPA + IR): Rats were orally treated with BPA daily for 4 weeks at the same dose given to group 5 then exposed to a single dose of IR (0.5 Gy). Group 8 (BPA + IR+ BA): Rats were orally treated with BPA daily for 4 weeks at the same dose given to group 5 then exposed to a single dose of IR (0.5 Gy), then treated with BA daily for 4 weeks at the same dose given to group 2. …”
Section: Methodsmentioning
confidence: 99%
“…Animals were divided randomly into 8 groups (6 animals per group): Group 1 (Control): Healthy animals supplied distilled water by gastric intubation daily for 4 weeks. Group 2 (BA): According to Mishra et al (2011), 23 Rats were treated orally with boswellic acid (BA) by gastric intubation in a dose of 50 mg/kg body weight a day for 4 weeks. Group 3 (IR): Rats were exposed to a single dose (0.5 Gy) of ionizing radiation as a low dose of radiation according to Shimura & Kojima (2014). 24 Group 4 (BA + IR): Rats were treated orally with BA every day at the same dosage as group 2 for 4 weeks, and were exposed to a single dose of IR (0.5 Gy). Group 5 (BPA): According to Amaravathi et al (2012), 25 Rats were treated orally with 500 mg/kg body weight Bisphenol A (BPA) daily over 4 weeks. Group 6 (BPA + BA): Rats were orally treated with BPA daily for 4 weeks at the same dose given to group 5 then treated with BA daily for another 4 weeks at the same dose given to group 2. Group 7 (BPA + IR): Rats were orally treated with BPA daily for 4 weeks at the same dose given to group 5 then exposed to a single dose of IR (0.5 Gy). Group 8 (BPA + IR+ BA): Rats were orally treated with BPA daily for 4 weeks at the same dose given to group 5 then exposed to a single dose of IR (0.5 Gy), then treated with BA daily for 4 weeks at the same dose given to group 2. …”
Section: Methodsmentioning
confidence: 99%
“…Another significant finding in this study is that exposure to the smallest dose (1 kGy) of gamma radiation resulted in an increase in the immunoidentification of almost 20% of the molecules tested. Although the beneficial effect of low ionizing radiation doses on the stimulation of the immune system in animal models is well known (Shimura and Kojima, 2014 ), it is mainly attributed to the stimulation of antibody production and specific cell types by products released by damaged cells (Yang et al , 2014 ). Hati et al ( 1990 ) reported that the antiserum produced against gamma-irradiated viper venom had better neutralizing efficiency when the antiserum was produced with the venom irradiated at a lower dose.…”
Section: Discussionmentioning
confidence: 99%
“…It is emerging as a promising therapeutic target with preliminary evidence that blockade of its receptor using tocilizumab leads to recovery in severe COVID-19 patients (13). These developing human data on the importance of IL-6 are supported by extensive animal data on the effects of lowdose radiation on a variety of animal diseases, including collagen-induced arthritis (CIA), experimental encephalomyelitis (EAE), and systemic lupus erythematosus, which were summarized in an extensive review (14). A unifying theme in these rodent models of human disease was that IL-6 levels were constitutively upregulated in the majority of the diseases and were significantly inhibited by lowdose radiation (15)(16)(17)(18).…”
Section: The Immune Response In Covid-19 Patientsmentioning
confidence: 92%